Loss of intrahepatic HBsAg expression predicts sustained response to peginterferon and is reflected by pronounced serum HBsAg decline. Issue 12 (20th January 2014) - Arends, P.; Rijckborst, V.; Zondervan, P. E.; Buster, E.; Cakaloglu, Y.; Ferenci, P.; Tabak, F.; Akarca, U. S.; Simon, K.; Sonneveld, M. J.; Hansen, B. E.; Janssen, H. L. A.
Summary There is a lack of knowledge regarding the effect of peginterferon (PEG‐IFN) on the expression of intrahepatic hepatitis B core and surface antigen (HBcAg and HBsAg) in chronic hepatitis B (CHB) and its relation with response to therapy. Fifty‐two HBeAg‐positive and 67 HBeAg‐negative CHB patients with paired liver biopsies taken at baseline and after 1 year of PEG‐IFN therapy were studied. After PEG‐IFN therapy, HBeAg‐negative patients showed a significant reduction in both intrahepatic HBcAg (P = 0.04) and HBsAg expression (P < 0.001). In contrast, a reduction in intrahepatic HBcAg expression was not observed in HBeAg‐positive patients, while a trend in reduction of intrahepatic HBsAg staining was found (P = 0.09). Post‐treatment, 7 (13%) HBeAg‐positive and 9 (14%) HBeAg‐negative patients had no expression of intrahepatic HBsAg. Patients without any intrahepatic HBsAg expression post‐treatment were more likely to achieve a combined response (HBeAg loss with hepatitis B virus (HBV) DNA <2000 IU/mL for HBeAg ‐positive and HBV DNA <2000 IU/mL and normal alanine aminotransferase for HBeAg‐negative CHB): 71% vs 5% for HBeAg‐positive (P < 0.001) and 60% vs 16% for HBeAg‐negative patients (P = 0.004), respectively. Moreover, a more profound decline of serum HBsAg was observed in patients with absence of intrahepatic HBsAg staining (3.1 vs 0.4 log IU/mL, P < 0.001 and 1.7 vs 0.4 log IU/mL, P = 0.005 for HBeAg‐positive and HBeAg‐negative CHB, respectively). In conclusion, PEG‐IFN reduces expression of intrahepatic HBsAg. Loss of HBsAg as assessed by immunohistochemistry from the liver predicts a sustained response and is reflected in a pronounced serum HBsAg decline.